ERROR MINIMIZATION OF ESTIMATE QUALITY BY EXPERT SYSTEMS - P. S. Serenkov; V. M. Romanchak; V. L. Gurevich (Приборы и методы измерений)
The complex analysis of information gathering and analyzing system in the context of quality management system (QMS) is given for the case when quality data are presented in the form of expert judgments. The concept of the correct expert QM system is proposed. This concept helps to minimize unobvious but rather essential errors of effectiveness and efficiency indices estimation.